PENGARUH KERAGAMAN PRODUK DAN KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN DI PB SWALAYAN METRO - Sari, Novita; Setiyowati, Selfi (Jurnal Manajemen Magister Darmajaya, 2017)
Consumer satisfaction is one key to the success of a business, this is because by satisfying the consumer, then the organization or company can increase its profits and be able to seize a much wider market share. In a customer-oriented modern organization, the consumer is the most important person in the company. A consumer is not dependent on a company, but a consumer-dependent company, one of the sources of customer satisfaction is the diversity of products and the quality of service that accompanies it. This study aims to determine how big the Effect of Product Diversity and Service Quality Against Consumer Satisfaction in PB Supermarkets Metro. This research type is Quantitative research. Data analysis technique used in this research is multiple linear regression analysis. The sampling technique used in this research is non probability sampling with purposive sampling method. Based on the technique, the number of samples is 96 respondents with 1 year research period is 2016. The result shows that product diversity has t value (4,195) bigger than t table value (1,661) so it can be concluded that product diversity influence to satisfaction consumer and service quality have t value (2,404) bigger than t table (1,661) so it can be concluded that service quality influence to consumer satisfaction. The diversity of products and service quality influence simultaneously to customer satisfaction is evidenced by the value of F arithmetic of 19.709 with F table of 3.09.Keywords: Product Diversity, Service Quality and Consumer Satisfaction